Transformasi Religius Narapidana Melalui Pembinaan Kerohanian Kristen di Lembaga Pemasyarakatan Kelas I Medan - Gelora Kurniawan Tarigan; Wido Cepaka Warih (Sosial Simbiosis : Jurnal Integrasi Ilmu Sosial dan Politik, 2024)
This study examines the religious transformation of inmates through the Christian spiritual guidance program at Class I Correctional Facility in Medan. The program aims to enhance inmates' spiritual awareness and behavioral change through worship, Bible study, and spiritual counseling. Using a qualitative research approach, data were collected through in-depth interviews, observations, and documentation studies. The results show that the Christian spiritual guidance program positively impacts inmates, contributing to significant behavioral changes, increased religious awareness, and deeper spiritual understanding. However, several challenges were identified, including limited resources, insufficient supervision, and a lack of adequate facilities. This study recommends improvements to the program’s implementation to achieve more sustainable outcomes and to address the existing challenges.